Painless osteoid osteoma of the distal phalanx of a toe. Issue 2 (15th February 2021) - Haoudou, Romeo; Malghem, Jacques; Galant, Christine; Docquier, Pierre-Louis
Abstract: Osteoid osteoma is a benign bone tumor, found in young subjects with typical intense focal pain, nocturnal exacerbation and favorable response to salicylates. Painless osteoid osteomas are rare and their diagnosis is difficult, especially whether their imaging appearance is not typical. We report the case of a 13-year-old boy with a spontaneous painless lesion of the distal phalanx of a toe. The main symptom was a swelling of the distal portion of the toe with an enlargement of its nail. The radiological aspect was not typical. A computed tomography showed a small lucent bone area within a focal hypertrophy of the phalangeal tuft and an osteoid osteoma was proposed as main diagnosis. The tumor was completely removed and the histopathological examination confirmed the diagnosis of osteoid osteoma. This clinical case shows that painless swelling of a toe may be indicative of an osteoid osteoma.